Orf virus como plataforma para vacinas vetoriais para suínos e bovinos - Martins, Mathias (2018)
Parapoxvirus ovis (PPVO) or orf virus (ORFV) is the causative agent of contagious ecthyma (or orf), a mucocutaneous disease that affects mainly sheep and goats. The ORFV belongs to the family Poxviridae, subfamily Chordopoxvirinae and genus Parapoxvirus. The virions are enveloped and their genome consist of a linear, double stranded DNA molecule of approximately 138 kb and contains at least 131 genes. ORFV has several biological and genomic properties that make it an attractive candidate for a vaccine vector. Therefore, it has been proposed as a vaccine platform to carry heterologous genes of veterinary interest. The first study reports the construction and characterization of two ORFV recombinants out of the parental strain ORFV IA82, expressing the rabies virus glycoprotein G (RABVG) at the loci of ORFV024 or ORFV121 genes, respectively, and an evaluation of their immunogenicity in swine and cattle. The in vitro characterization showed that the recombinants ORFVΔ024RABV-G and ORFVΔ121RABV-G retained their replicative capacity in cell culture, compared to the parental virus. The recombinant viruses expressed RABV-G efficiently even after 10 passages in cell culture, demonstrating the stability of the inserts. Immunization of swine and cattle with ORFVΔ024RABV-G and ORFVΔ121RABV-G resulted in a robust neutralizing antibody response against the rabies virus (RABV). The neutralizing antibodies titers induced by ORFVΔ121RABV-G in swine and cattle were higher than those induced ORFVΔ024RABV-G, indicating a higher efficiency of ORFVΔ121 as a vector in these species. In a second study, ORFV mutants with individual deletions of genes ORFV112, ORFV117 or ORFV127 were constructed, characterized in vitro and inoculated experimentally in lambs. When characterized in vitro, the deletion mutants replicated in ovine fetal turbinate (OFTu) cells with the same efficiency of the parental virus, with no changes in replication kinetics, plaque size and morphology. Experimental inoculation of lambs at the mucocutaneous junction of the oral commissure demonstrated that individual deletions of ORFV112, ORFV117 or ORFV127 genes did not result in obvious changes in virulence, since the mutants produced lesions as severe as those induced by the parental virus. However, resolution of the lesions apparently occurred more rapidly in the animals inoculated with the mutant virus than in those inoculated with the parental virus. In addition, the mutant viruses were excreted from the lesions in lower titers than those of the parental virus. These results demonstrated that genes ORFV112, ORFV117 and ORFV127 are not essential for viability of ORFV in vitro and interfere only partially in ORFV virulence in lambs. A third study was conducted to compare the magnitude and duration of the serological response induced in cattle by four commercial vaccines against RABV. After two vaccinations 30-days apart, the animals received a booster vaccination one year later, and were subjected to serological tests for virus neutralizing (VN) antibodies at different intervals after vaccination and booster. The four vaccines were found to be suitably immunogenic, e.g., induced high titers of VN antibodies in the animals after primary vaccination. However, a marked decrease in antibody levels was observed prior to the annual booster. Therefore, it is recommended that annual revaccination protocols be reviewed, since part of the vaccinated animals no longer have adequate antibodies levels one year after vaccination. In summary, the experiments presented in this thesis demonstrate that ORFV represents a promising platform for vectoring vaccine antigens in swine and cattle and that, in addition to the ORFV024 and ORFV121 genes, loci ORFV112, ORF117 and ORFV127 can also be used for heterologous gene insertion.